Exploring engagement of users of Global Englishes in a community of inquiry. (June 2021) - Smidt, Esther; Chau, Meng Huat; Rinehimer, Eric; Leever, Patricia
Abstract: The Community of Inquiry (CoI) framework has been extensively studied. While prior research has investigated the development and validity of the CoI theoretical construct, few studies have focused on the interdependent Cognitive, Social and Teaching Presences of the framework and none have been conducted based on a positive framing of Global Englishes (GE) which directly challenges a monolingual ideology. This mixed methods study considers how GE users in a Second Language Acquisition postgraduate course at a research university in Malaysia experienced these three Presences in their course, and how knowledge was collaboratively constructed in relation to their experience with these Presences. Data sources consisted of the CoI surveys and discussion board posts. Analysis of these posts focused on the relationship between CoI Presences, GE user participation and knowledge construction. Findings suggest that the GE users actively constructed knowledge collaboratively in the CoI, and that they took on varied roles which demonstrated the three Presences. This study makes an empirical contribution to the body of research on GE users and a functioning CoI in asynchronous discussion boards. Additionally, it highlights the importance and potential value of a conscious, empowering framing of students as GE users in transforming research possibilities and outcomes in Applied Linguistics.